Bright luminescent lithium and magnesium carbene complexes. Issue 21 (27th April 2021) - Pinter, Piermaria; Schüßlbauer, Christoph M.; Watt, Fabian A.; Dickmann, Nicole; Herbst-Irmer, Regine; Morgenstern, Bernd; Grünwald, Annette; Ullrich, Tobias; Zimmer, Michael; Hohloch, Stephan; Guldi, Dirk M.; Munz, Dominik
Abstract : Lithium- and magnesium complexes of a CNC pincer ligand composed of carbazole and two mesoionic carbenes are bright luminescent, because the metals prevent molecular distortions upon excitation. Abstract : We report on the convenient synthesis of a CNC pincer ligand composed of carbazole and two mesoionic carbenes, as well as the corresponding lithium- and magnesium complexes. Mono-deprotonation affords a rare "naked" amide anion. In contrast to the proligand and its mono-deprotonated form, tri-deprotonated s -block complexes show bright luminescence, and their photophysical properties were therefore investigated by absorption- and luminescence spectroscopy. They reveal a quantum yield of 16% in solution at ambient temperature. Detailed quantum-chemical calculations assist in rationalizing the emissive properties based on an Intra-Ligand-Charge-Transfer (ILCT) between the carbazolido- and mesoionic carbene ligands. (Earth-)alkali metals prevent the distortion of the ligand following excitation and, thus, by avoiding non-radiative deactivation support bright luminescence.